THE CHALLENGES OF ENGLISH TEACHERS IN TEACHING ONLINE ENGLISH BY USING EDULEARNING APPLICATION AT SMP MUHAMMADIYAH 4 - Muhammad - Noval; Nargis - -; Aidil Syah Putra (Globish: An English-Indonesian Journal for English, Education, and Culture, 2022)
This study aims to find out about the challenges of English teachers in teaching online English by using the EduLearning application, where the study examines what kind of challenges that the English teachers face during the online course using EduLearning application and also how do they deal with the challenges itself, There are two objectives in this study, they are 1) To know what are the challenges that English teachers face in online teaching using EduLearning application. 2) To know how do English Teachers deal with the challenges in online teaching using EduLearning at SMP Muhammadiyah 4. The researcher used data collection techniques, namely interviews and questionnaires. The interview is an online interview that was asked to three English teachers with the same questions of each, and the questionnaire was given through Google form. The first question shows that there are five challenges that were encountered by the English Teachers by using the EduLearning application, namely internet connection, media, lack of interaction between students and teachers, limited ability, and technical problems. And for the second question shows that there are four solutions, namely, school-provided computer laboratory to be used by students, the variation in teaching online, the shifting application, and the need for training.Keywords: Online teaching, EduLearning application, Challenges.